2022
DOI: 10.3390/gels8070392
|View full text |Cite
|
Sign up to set email alerts
|

Silica-Based Aerogel Composites Reinforced with Reticulated Polyurethane Foams: Thermal and Mechanical Properties

Abstract: In this work, silica aerogel composites reinforced with reticulated polyurethane (PU) foams have been manufactured having densities in the range from 117 to 266 kg/m3 and porosities between 85.7 and 92.3%. Two different drying processes were employed (ambient pressure drying and supercritical drying) and a surface modification step was applied to some of the silica formulations. These composites, together with the reference PU foam and the monolithic silica aerogels, were fully characterized in terms of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…These results confirm that the addition of an organic polymer drastically increases the thermal conductivity of hybrid aerogels. Hence, the thermal conductivity values of the TGP_X aerogels in the present work from 22.4 to 30.6 mW/mK are comparable to those of these previously reported organic–inorganic hybrid aerogels [ 38 , 52 , 53 , 54 , 55 ], owing to the synergy among the thermally less conductive PACA polymer (60 mW/mK) [ 56 ] and the silica aerogel.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…These results confirm that the addition of an organic polymer drastically increases the thermal conductivity of hybrid aerogels. Hence, the thermal conductivity values of the TGP_X aerogels in the present work from 22.4 to 30.6 mW/mK are comparable to those of these previously reported organic–inorganic hybrid aerogels [ 38 , 52 , 53 , 54 , 55 ], owing to the synergy among the thermally less conductive PACA polymer (60 mW/mK) [ 56 ] and the silica aerogel.…”
Section: Resultssupporting
confidence: 88%
“…For example, Ghica et al [ 52 ] observed an increase in thermal conductivity from 31.3 to 85.4 mW/mK after the reinforcement of a silica aerogel with optimized polyamide pulps. Moreover, Merillas et al [ 53 ] analyzed that the synthesized polyurethane-reinforced silica composite aerogel exhibited enhanced thermal conductivity from 33.4 to 52.5 mW/mK. Similarly, Ilhan et al [ 54 ] and Hae-Noo-Ree Jung et al [ 55 ] reported improved thermal conductivity of hydrophobic silica aerogels to around 41 and 131 mW/mK with the addition of polystyrene and poly(methyl methacrylate), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rao et al investigated the effect of various replacement solvents on the pore structure of silica aerogels, and the corresponding results proved that the n -heptane solvent with low-surface tension was the optimal selection for the preparation of silica aerogel in the process of ambient drying. For surface modification, the alkylated silanes are the ideal precursors, which mainly include methyltrimethoxysilane (MTMS), , methyltriethoxysilane, vinyltrimethoxysilane (VTES), trimethylmethoxysilane (TMMS), trimethylchlorosilane (TMCS), and hexamethyldisilazane, etc . For instance, Yang et al prepared highly elastic hydrophobic silica aerogels using VTES and MTMS as composite precursors.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained samples showed excellent insulating capacities, reaching values between 14.0 and 12.3 mW/m•K for the surface-modified composites that were dried under supercritical conditions. Merillas et al [24] prepared silica aerogel composites reinforced with reticulated PU foam by the sol-gel method and under both ambient and supercritical drying pressures. The carbonyl and amine groups of the polyurethane foam could establish a chemical interaction with the silica matrix, promoting an effective interaction, thus improving the mechanical properties of the silica aerogel.…”
Section: Introductionmentioning
confidence: 99%